INVESTIGATION OF LOCALIZED ELECTROMAGNETIC FIELD IN A SUBWAVELENGTH METALLIC SLIT - Arakelyan, Sh.Kh. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2017)
Electromagnetic field localization in a subwavelength metallic slit by a thermo-elastic optical indicator microscope (TEOIM) was investigated. As an indicator for the TEOIM system a slide glass with sizes of 20× 20×0.5 (mm) was used, on the surface of which an Al film of 20 nm thickness was vaporized using the vacuum evaporation technique, with various slit width (10-50 μ m). Strongly localized electromagnetic field has been exited in the slits by 50 GHz generator and was visualized by a TEOIM. The waveguide properties of the system were characterized by COMSOL Multiphysics^ additionally. The simulation results are in good agreement with the visualization data set.